Multi-patch IGA associated with Nitsche’s method for morphogenesis of complex free-form surface - Song, Ziling; Yu, Tiantang; Wang, Lin; Bui, Tinh Quoc (Engineering analysis with boundary elements, 2025)
The analysis of complex multipatch structures has been solved with numerical tools, however, isogeometric shape optimization has not yet been applicable for designing free-form surface. Benefiting from the key concept of isogeometric analysis (IGA) for integration of design and analysis, a morphogenesis method is presented for shape optimization of complex free-form surfaces, especially built with multipatches. The optimization is based on control points’ information to adjust the nodal positions to achieve a structure with the minimum strain energy by particle swarm optimization. In this setting, the constraints of control point on both sides are used to connect interfaces between patches during shape modifications. For the analysis, we introduce the Kirchhoff–Love shell element and Nitsche’s method to couple non-conforming patches. The NURBS composition defines the geometry of the shell while the displacement field is approximated using the same spline functions as the free-form surface. The effectiveness and performance of the proposed method are verified by some numerical examples, and the mechanical properties of the optimized structure are greatly improved. •Morphogenesis of free-form surface within isogeometric shape optimization is presented.•Multi-patch technology is used to exactly represent complex free-form surface.•Kirchhoff–Love shell element is combined with Nitsche’s method.•PSO algorithm is adopted to obtain the optimal free-form surface.•Numerical examples show the great performance of the present method.